Investigation on the effets of physical parameters of terahertz bow-tie photoconductive antennas to their performance / Ameerul Faisal Asmari - Asmari, Ameerul Faisal (2014)
The physical parameters of bow-tie PC A is investigated in this project, their effects and relationship with resonant frequency have been reviewed and discussed. The dimensions at 1 terahertz (THz) resonant frequency for bow-tie PCA has been used as the reference for the parameter sweep method. Analysis has been done using data from the parameter sweep simulation result. The physical parameter chosen is dipole length, angles of tapered flare, gap length, gap width, substrate length, substrate width, substrate thickness and copper thickness. 10 dimension is taken for each parameter and their relationship to the resonant frequency is illustrated in graph. The simulation is done by using CST Studio Suite and plotted by Matlab software.